Bridging Cultures: Translation of Cultural Terms in Leila S. Chudori’s “Pulang”: Melintasi Budaya: Terjemahan Istilah Budaya dalam “Pulang” Karya Leila S. Chudori - Aprianto Sugi Arto Putra, Danu; Suyudi, Ichwan (Jurnal Penerjemahan, 2025)
This research focuses on analyzing the categories of cultural terms, the translation techniques used, and the quality of translation in Leila S. Chudori’s novel “Pulang” and its English version “Home.” This study employs a qualitative descriptive method, which allows the researcher to examine and interpret the meanings of cultural terms within their social and cultural contexts. The qualitative descriptive method is applied through document analysis and supported by investigator and theoretical triangulation to ensure data credibility. The data of this research consist of two types: (1) linguistic data in the form of words, phrases, and clauses containing cultural terms in both the source and target texts; (2) translation data, which include the translation techniques used to transfer cultural meaning as well as the translation quality data, which include assessments of accuracy, acceptability, and readability. The researcher identified 134 data related to cultural terms and their translation. Five categories of cultural terms were found, with material culture appearing as the dominant category (70 data). Eleven translation techniques were identified, among which borrowing was the most frequently used technique (39 data). The dominance of the borrowing technique suggests that many cultural terms in “Pulang” have no direct or natural equivalents in English, causing the translator to retain the original terms to preserve cultural meaning. In conclusion, this study emphasizes the significance of understanding cultural categories and translation techniques when translating cultural terms.  It suggests that future researchers may expand the analysis by using additional theoretical frameworks or comparing various translations in order to gain a better understanding of cultural representation in translated texts.